Staphylococcus aureus α-Toxin Induces Acid Sphingomyelinase Release From a Human Endothelial Cell Line - Krones, David; Rühling, Marcel; Becker, Katrin Anne; Kunz, Tobias C.; Sehl, Carolin; Paprotka, Kerstin; Gulbins, Erich; Fraunholz, Martin (Frontiers in Microbiology, 2021)
Staphylococcus aureus (S. aureus) is well known to express a plethora of toxins of which the pore-forming hemolysin A (α-toxin) is the best-studied cytolysin. Pore-forming toxins (PFT) permeabilize host membranes during infection thereby causing concentration-dependent effects in host cell membranes ranging from disordered ion fluxes to cytolysis. Host cells possess defense mechanisms against PFT attack, resulting in endocytosis of the breached membrane area and delivery of repair vesicles to the insulted plasma membrane as well as a concurrent release of membrane repair enzymes. Since PFTs from several pathogens have been shown to recruit membrane repair components, we here investigated whether staphylococcal α-toxin is able to induce these mechanisms in endothelial cells. We show that S. aureus α-toxin induced increase in cytosolic Ca2+ in endothelial cells, which was accompanied by p38 MAPK phosphorylation. Toxin challenge led to increased endocytosis of an extracellular fluid phase marker as well as increased externalization of LAMP1-positive membranes suggesting that peripheral lysosomes are recruited to the insulted plasma membrane. We further observed that thereby the lysosomal protein acid sphingomyelinase (ASM) was released into the cell culture medium. Thus, our results show that staphylococcal α-toxin triggers mechanisms in endothelial cells, which have been implicated in membrane repair after damage of other cell types by different toxins.